Enhancing mathematical modelling competency through textbook design - Højgaard , Tomas (American Journal of Education and Learning, 2025)
Around the world, mathematics school curricula increasingly use learning goals in an effort to capture different kinds of processes that students should master. For primary and secondary mathematics education in Denmark, these ambitions are expressed in terms of a set of mathematical competencies. However, implementing such competencies into actual teaching practice has proved challenging particularly when it comes to mathematical modelling competency. Matematrix is a Danish mathematics textbook system for grades K-9, designed to support mathematics teachers in overcoming this challenge. In this article, I as one of the designers and authors of these textbooks describe and exemplify their design and the analytical foundations on three different levels: the overall structuring of the books’ content, the focal points for each chapter, and the development of different kinds of tasks for students to work with. In these descriptions, I focus on and provide concrete examples of how my colleagues and I sought to support teachers in facilitating their students’ development of mathematical modelling competency. This analytical focus leads me to distinguish between and exemplify mathematization tasks of short duration, constructive modeling tasks of short duration, and inquiry-based projects of longer duration focusing on either the constructive or the receptive facets of mathematical modelling competency.